Active smoking among people with diabetes mellitus or hypertension in Africa: a systematic review and meta-analysis - Noubiap, Jean Jacques (Sci Rep, 2019)
The objective was to summarize existing data on the prevalence of active tobacco smoking among patients with hypertension or diabetes mellitus in Africa. We searched PubMed, EMBASE, and AJOL to include studies published from January 01, 2000 to August 23, 2017 reporting on the prevalence of active smoking in individuals aged ≥15 years with hypertension or diabetes mellitus residing inside Africa. We used a random-effects meta-analysis model to pool studies. The pooled prevalence of active smoking among patients with hypertension or diabetes was 12.9% (95%CI: 10.6–15.3; 50 studies; 16,980 patients) and 12.9% (95%CI: 9.6–16.6; 42 studies; 18,564 patients), respectively. For both conditions, the prevalence of active smoking was higher in males than in females (p < 0.001), and in Northern compared to sub-Saharan Africa (p < 0.001). There was no difference between urban and rural settings, and between community-based and hospital-based studies, except for patients with diabetes for whom the prevalence was higher in hospital-based studies (p = 0.032). The prevalence of active smoking is high among patients with hypertension or diabetes mellitus in Africa, with the heaviest burden in Northern Africa. Interventions for smoking prevention or cessation should be implemented in these high risk populations, targeting particularly the males.